Mid-arm and Chest Circumferences for Estimating Low Birthweight - Achmad Surjono (Paediatrica Indonesiana, 1993)
A prospective study was conducted to assess the diagnostic performance of mid-arm and chest circumferences on low birth weights in 1033 singleton newborn infants. The proportion of low birth weight was 11.7%. Strong correlations on birth weight (P<0.001) were found for mid-arm (r-0.85) and chest (r=0.86) circumferences. A mid-arm circumference of ≤9,5 cm was considered as cut-off level for low birth weight, with a sensitivity of 0.818, specificity 0.956 and positive predictive value 0. 712. Whereas that of chest circumference wa ≤29.5 cm with a sensitivity of 0. 785, specificity 0.895 and positive predictive value 0.497. Receiver operating characteristic (ROC) curves were used to compare their diagnostic accuracy. The area under these two ROC(± SE) were 0.954 ± 0.011 for mid-arm and 0.945 ± 0.012 for chest circumferences, respectively. Both areas showed significant differences with the area under chance line. No statistically significant difference was found between the area under ROC of mid-arm and chest circumferences. The results showed that mid-arm and chest circumferences as simple and reliable measurements can be used in estimating low birth weight, in areas where the accurate weighing of newborn infants is not feasible.